Pathogenic roles of CXCL10 signaling through CXCR3 and TLR4 in macrophages and T cells: relevance for arthritis - Jong-Ho Lee; Bongjun Kim; Won Jong Jin; Hong-Hee Kim; Hyunil Ha; Zang Hee Lee (Arthritis Research & Therapy, 2017)
Abstract Background Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by uncontrolled joint inflammation and destruction of bone and cartilage. We previously reported that C-X-C motif chemokine 10 (CXCL10; also called IP-10) has important roles in joint inflammation and bone destruction in arthritis. However, the specific mechanisms by which CXCL10 regulates the recruitment of inflammatory cells and the production of osteoclastogenic cytokines in RA progression are not fully understood. Methods Bone marrow-derived macrophages and CD4+ T cells were isolated from wild-type (WT), Cxcl10 –/–, and Cxcr3 –/– mice. CXCL10-induced migration was performed using a Boyden chamber, and CXCL10-stimulated production of osteoclastogenic cytokines was measured by quantitative real-time PCR and ELISA. Collagen antibody-induced arthritis (CAIA) was induced by administration of collagen type II antibodies and lipopolysaccharide to the mice. Clinical scores were analyzed and hind paws were collected for high-resolution micro-CT, and histomorphometry. Serum was used to assess bone turnover and levels of osteoclastogenic cytokines. Results CXCL10 increased the migration of inflammatory cells through C-X-C chemokine receptor 3 (CXCR3)-mediated, but not toll-like receptor 4 (TLR4)-mediated, ERK activation. Interestingly, both receptors CXCR3 and TLR4 were simultaneously required for CXCL10-stimulated production of osteoclastogenic cytokines in CD4+ T cells. Furthermore, calcineurin-dependent NFATc1 activation was essential for CXCL10-induced RANKL expression. In vivo, F4/80+ macrophages and CD4+ T cells robustly infiltrated into synovium of WT mice with CAIA but were significantly reduced in both Cxcl10 –/– and Cxcr3 –/– mice. Serum concentrations of osteoclastogenic cytokines and bone destruction were also reduced in the knockout mice, leading to attenuated progression of arthritis. Conclusion These findings highlight the importance of CXCL10 signaling in the pathogenesis of RA and provide previously unidentified details of the mechanisms by which CXCL10 promotes the development of arthritis.